(untitled) (Global Scientific Review, 2024)
Nanotechnology has witnessed a revolution in our current era and has penetrating into consumer industries, biomedical and electronic fields, and environmental treatments, due to the chemical-physical properties of nanoparticles, especially metal ones, and the advantage of large surface area to volume. Thus, the growing consumption of these minutes has increased the exposure of living organisms to potential risks associated with their toxicity, especially vital organs as liver. The present review summarizes the potential hepatotoxicity in vivo (rat model) of experimentally exposed metal nanoparticles or their oxides. Most of the literature indicates that the induced hepatotoxicity is due to oxidative stress, cytotoxicity, and disturbance of liver function depending on the concentrations and method of exposure to these nanoparticles. Therefore, the toxic potential must be taken into account and the damage that may be caused to other vital organs in the body must be constantly e v a l u a t e d i n o r d e r t o r e a c h s a f e u s e o f t h e s e n a n o p a r t i c l e s